?STUDIES OF THE POLYNUCLEAR COMPLEXES OF LABILE LIGANDS OF VITAMIN B 1 AND Zn (II), Cd (II) AND Hg (II) WITH Fe (III) (Biological Sciences - PJSIR, 2003)
The ligands (complex salts) of vitamin B1 (H Vit.) and the chlorides of Zn, Cd and Hg with the general formula, [HVit]+ 2 [MCl4]- 2 were prepared and their interactions with iron (III) investigated. It was found that the complex salts of Zn and Cd produced the dinuclear complexes and that of mercury produced a complex without the thiamine moiety. The possible reason for the absence of a Hg complex similar to those of Zn and Cd may be that large size of mercury ion. The complexes were characterized by elementary analyses, infrared and visible spectra, magnetic moment and conductivity measurements.